Optical microfiber devices based laser and sensor applications / Md. Jahid Faruki - Md. Jahid , Faruki (2018)
Optical microfiber has attracted many researchers attention due to many interesting properties such as strong evanescent fields, tight optical confinement, compact size and easy integration with the optical system. All these advantages can be used to develop various lasers and refractive index-based sensors. In this work, the microfiber has been fabricated using the flame brushing technique and it has been used in both laser and sensor applications. The microfiber has been used as a filter device to generate dual wavelength fiber laser by taking the advantage of the interference pattern and the unique arrangement of polarization controller (PC). The proposed microfiber device can generate highly stable and tunable dual wavelength with spacing between 0.40 nm to 3.32 nm (corresponding to frequency from 49.4 GHz to 409 GHz). The application of microfiber in pulse laser (Qswitched and mode-locked) generation is demonstrated where graphene coated microfiber device has been utilized as a saturable absorber device. A new Poly (N-vinyl Carbazole) - Polypyrrole/Graphene Oxide (PNVC-PPy/GO) nano-composite material has been deposited on a tapered part to fabricate microfiber based saturable absorber device, and a passively Q-switched fiber laser has been demonstrated with repetition rates from 25.2 kHz to 42.7 kHz. Meanwhile, microfiber based mode locked pulse generation is also demonstrated where pulse trains with a pulse width of 3.46 ps, a 3dB optical bandwidth of 11.82 nm and a repetition rate of 920 kHz are obtained. Moreover, this study has also investigated the mechanism of tuning the mode-locked pulses by stretching the microfiber. The mode-locked pulse is tuned over a span of 4.4 nm (from 1560.6 nm to 1556.2) by stretching the tapered fiber from 0 to 100 μm (strain). Furthermore, microfiber based devices such as dual tapered optical microfiber inline Mach-Zhender interferometer (OMI-MZI) and microfiber knot resonator (MKR) have been exploited in sensor applications. An OMI-MZI has been used as a temperature sensor, and the sensitivity has been observed before and after the coating with PNVC-PPy/GO. The uncoated and PNVC-PPy/GO coated OMI-MZI exhibited a sensitivity of 30.4 pm/oC and 37.1 pm/oC, respectively. Thereafter, a refractive index based humidity sensor has also been demonstrated by using microfiber knot resonator (MKR) where uncoated MKR showed a sensitivity of 1.3 pm/%RH and TiO2 nanoparticles coated MKR showed a sensitivity of 2.5 pm/%RH. Further, the results indicate that the optical microfiber is highly potential for various sensing and lasing applications.